Physicochemical and bacteriological assessment of ricemill wastewater discharged into river Benue, Nigeria - Adeniyi Olarewaju Adeleye; Amoo Afeez Oladeji; Bate Garba Barde; Sadiq Ismaila Shina; Ugba Samuel (Association for Scientific Computing, Electronics, and Engineering (ASCEE), 2021)
Rapid industrialization affects the environment in different ways through indiscriminate disposal of large amount of wastewater into the surrounding water bodies thereby causing serious problems to the environment. This study was conducted to assess the suitability of the ricemill wastewater being discharged into River Benue. Wastewater was sampled from point of discharge (sampling point A) and 20 meters away from the final entry into river Benue (sampling point B). Standardized methods were employed to analyze biochemical oxygen demand (BOD), chemical oxygen demand (COD), total dissolved solids (TDS), total heterotrophic count (THC), nitrate, phosphate, sulphate and pH in the sampled wastewater. Results were generated and compared with permissible standards Results generated from the analyses indicate that in sampling point A, pH ranged from 4.28 to 5.23, TDS ranged from 1478 - 1615 mg/L while THC ranged from1540 - 1600 cfu/ml. In point B, (BOD) ranged from 4.8 - 3.6 mg/L, (COD) ranged from 4.1 - 3.1mg/L, (TDS) 586 - 348mg/L, (THC) 608 - 512 cfu/ml and pH 7.32 - 6.43. Considering these results, (TDS), (THC), nitrate and THC were above permissible limits of World Health Organisation (WHO) and National Environmental standards and regulations Enforcement Agency (NESREA) respectively. Owing to these results, treatment measures and regulatory policies are suggested with a view to checkmating the abuse of river Benue through indiscriminate disposal of wastewater so as to avert imminent dangers it might likely pose to aquatic ecological system.